A catalog of Anisopodidae (Diptera) from Chile - González, Christian R; Elgueta, Mario; Amorim, Dalton De Souza (Zootaxa, 2019)
A catalog of the Anisopodidae from Chile is provided. All valid names and synonyms are presented, summing up five species in two genera for the country. All references known to us from the taxonomic and biological literature are provided, including information about name, author, year of publication, page number, type species, type locality, distribution, and references. We keep Tonnoirina Amorim & Tozoni as a synonym of Sylvicola and Neomesochria Amorim & Tozoni as a synonym of Mycetobia.